Enhancing Active-Learning Through Interactive-Video for Teaching Pottery In Selected Upper-Basic Schools, Nigeria - Abdulganiyu Alasela Amosa; Omotayo Olabo Obielodan; Oyeronke Olufunmilola Ogunlade; Kamal Jimoh Muhamed (IJER (Indonesian Journal of Educational Research), 2019)
The use of interactive-video for teaching is a possible solution to the inadequacy of instructional materials because it enhances acquisition of practical skills in basic technology. The objective of this study was to determine the difference between performance of students taught using interactive-video and their counterparts taught using expository method. Thus, one research question was raised and one hypothesis was tested. The population for the study comprised all upper-basic students in Kwara State, Nigeria. Thus, the sample comprised of 32 students each from the two-sampled upper-basic schools. The sampled schools were randomly assigned to experimental and control groups. The quasi-experimental design was adopted. One research question raised was answered through its corresponding hypothesis one, which was tested through the Analysis of Covariance. Thus, the finding of study revealed that significant difference was established between the students taught using the interactive-video and their counterparts taught using expository method in favour of those who used the interactive-video. Therefore, the study concluded that interactive-video affords greater interaction between the teacher and students. In addition, it greatly enhanced the academic achievement of students. The study recommended that interactive-video should be permanently involved in the teaching of basic technology.